The Influence of Inclusive Education Management and Teacher Competence on Student Participation in Learning - Istiarsyah, Istiarsyah; Nurhabibah, Nurhabibah; Anizar, Anizar; Amelyani, Amelyani; Rafika, Irda; Basneldi, Basneldi (Westscience Press, 2026)
This study investigates how inclusive education management and teacher competence contribute to expanding student participation in the learning process. A quantitative research design was employed, involving 125 respondents from inclusive education settings. Data were collected using a structured questionnaire measured on a Likert scale and analyzed using SPSS version 25. The results of multiple linear regression analysis reveal that inclusive education management has a positive and significant effect on student participation, indicating that effective leadership, inclusive policies, and supportive management practices foster more engaging learning environments. Teacher competence also shows a positive and significant influence on student participation and emerges as the stronger predictor, highlighting the critical role of teachers’ pedagogical skills, classroom management, and inclusive instructional strategies in encouraging active student engagement. Simultaneously, inclusive education management and teacher competence explain a substantial proportion of variance in student participation. These findings emphasize that inclusive education is most effective when supported by both strong organizational management and competent teachers. The study provides empirical evidence to inform school leaders and policymakers in developing integrated strategies to enhance student participation through inclusive education practices.